2018
DOI: 10.3389/fimmu.2018.02618
|View full text |Cite
|
Sign up to set email alerts
|

CD137 (4-1BB) Signalosome: Complexity Is a Matter of TRAFs

Abstract: CD137 (4-1BB, Tnsfr9) is a member of the TNF-receptor (TNFR) superfamily without known intrinsic enzymatic activity in its cytoplasmic domain. Hence, akin to other members of the TNFR family, it relies on the TNFR-Associated-Factor (TRAF) family of adaptor proteins to build the CD137 signalosome for transducing signals into the cell. Thus, upon CD137 activation by binding of CD137L trimers or by crosslinking with agonist monoclonal antibodies, TRAF1, TRAF2, and TRAF3 are readily recruited to the cytoplasmic do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
99
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 121 publications
(169 reference statements)
0
99
2
Order By: Relevance
“…Additionally, the CD137L expression on HCC‐827 cells significantly induced IFN‐γ production because this could be completely inhibited by treatment with anti‐CD137 mAb. It has been suggested that CD137 is sensitive to stimulation by CD137L, so even these low expression levels might be sufficient to trigger CD137 signaling upon interaction with CD137L. More interestingly, we found that anti‐CD137 mAb can also induce the expression of PD‐L1 in lung cancer cells and synergize with IFN‐γ.…”
Section: Discussionmentioning
confidence: 53%
“…Additionally, the CD137L expression on HCC‐827 cells significantly induced IFN‐γ production because this could be completely inhibited by treatment with anti‐CD137 mAb. It has been suggested that CD137 is sensitive to stimulation by CD137L, so even these low expression levels might be sufficient to trigger CD137 signaling upon interaction with CD137L. More interestingly, we found that anti‐CD137 mAb can also induce the expression of PD‐L1 in lung cancer cells and synergize with IFN‐γ.…”
Section: Discussionmentioning
confidence: 53%
“…1 As early as 1975, Lafferty and Cunningham 2 proposed that in addition to antigenic stimuli, full activation of antigen-specific T cells required secondary signals from antigen-presenting cells (APCs). 3,4 Costimulatory receptors of the Ig superfamily tend to activate phosphatidylinositol 3-kinase (PI3K) leading to protein kinase B (Akt) and downstream nuclear factor jB (NF-jB) activation, while TNFR superfamily members preferentially recruit and activate TNF receptorassociated factors (TRAFs) to potentiate NF-jB activation. 3 Later observations confirmed that antigenic stimulation without sufficient costimulation results in T cell anergy and T cell susceptibility to activation-induced cell death (AICD).…”
Section: T Cell Costimulationmentioning
confidence: 99%
“…Confirmation of this classical two-signal hypothesis was achieved with the generation of antibodies that block costimulatory molecules, and the cloning of B7 family members CD80 and CD86, which are ligands for the prototypical T cell costimulatory receptor CD28. 3,4 Examples of costimulatory molecules expressed by T cells include CD28, ICOS, CD27, 4-1BB, OX40 and CD40L (see Table 1). 3 Broadly defined as cell surface molecules that can transduce signals into T cells to enhance TCRmediated signals, 1 most costimulatory receptors belong to the immunoglobulin (Ig) or tumor necrosis factor receptor (TNFR) superfamilies, and bind to ligands expressed by activated or licensed APCs.…”
Section: T Cell Costimulationmentioning
confidence: 99%
See 2 more Smart Citations